Early echocardiographic signs of diastolic dysfunction predict acute kidney injury in cirrhotic patients. Issue 11 (4th September 2020) - Wu, Pei-Shan; Wang, Ying-Wen; Tai, Cheng-Chun; Hsieh, Yun-Cheng; Lee, Pei-Chang; Huang, Chin-Chou; Huang, Yi-Hsiang; Hou, Ming-Chih; Lin, Han-Chieh; Lee, Kuei-Chuan
Abstract : Background: Cardiovascular dysfunction in cirrhotic patients affects survival and the development of cirrhotic complications. We aimed to evaluate potential echocardiographic parameters to predict mortality and acute kidney injury (AKI) in cirrhotic patients. Methods: A total of 103 cirrhotic patients who underwent echocardiography between February 2009 and August 2016 in Taipei Veterans General Hospital were retrospectively enrolled. Cardiac function was evaluated using transthoracic two-dimensional echocardiography with tissue Doppler imaging. Cox hazard regression analysis was used for assessing predictors for 1-year mortality and AKI within 1 year. Results: Baseline echocardiographic parameters were similar between survivors (n = 92) and nonsurvivors (n = 11). Lower serum levels of albumin, as well as higher albumin-bilirubin (ALBI) scores, Child-Pugh scores, and model for end-stage liver disease scores were observed in nonsurvivors. Cox proportional hazard regression analysis revealed Child-Pugh score as the only predictor of 1-year mortality. Baseline serum creatinine (Cr) > 1.5 mg/dL, total bilirubin > 2 mg/dL, and a higher E/e′ ratio predict occurrence of AKI within 1 year. Among patients with serum Cr < 1.5 mg/dL, an increased atrial filling velocity and higher ALBI scores predict AKI occurrence within 1 year. Conclusion: Severity of underlying liver disease but not echocardiographic parameters predicts 1-year mortality in cirrhosis. Early echocardiographic signs of diastolic dysfunction and higher ALBI scores may predict development of AKI in cirrhotic patients with serum Cr < 1.5 mg/dL.